Molecular Characteristics and Antibiotic Resistance Profiles of Klebsiella Isolates in Mthatha, Eastern Cape Province, South Africa - Vasaikar, Sandeep; Obi, Larry; Morobe, Isaac; Bisi-Johnson, Mary (Hindawi Publishing Corporation, 2020)
International Journal of Microbiology, Volume 2017, Article ID 8486742, 7 pages